CONSUMPTION PATTERNS AND NUTRITIONAL STATUS OF ADOLESCENTS AND PARENTS WITH DIABETES MELLITUS (DM) - Teuku, Jamni; Afdhal, Afdhal; Nugroho, Erlangga Galih Zulva; Erwandi; Sitio, Roma; Oktabina, Rizki Wan (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Teenagers more often consume foods that are high in fat and glucose than vegetable and fruit consumption. This can trigger the onset of diabetes mellitus, especially in adolescents who have Diabetes Mellitus (DM) parents. The purpose of this study was to determine the differences in consumption patterns and status between adolescents and parents of DM and not DM. This cross sectional study involved 42 adolescents as samples, consisting of 21 adolescents with DM parents and 21 adolescents who were not DM parents, randomly using simle rendom sampling technique, the differences between variables were analyzed using the Independent T-test and Mann Whitney test (α=0.05). The results showed that there were no differences in the consumption patterns of high Glycaemic Index (GI) foods (p = 0.229) and fruit and vegetables (p = 0.14) between adolescents with DM parents and non-DM parents, but adolescents with DM parents tended to consume more high GI foods than adolescents with non-DM parents. There were differences in nutritional status between adolescents with DM parents and non-DM parents (p = 0.036). The conclusion of this study is that most adolescents with DM parents are very overweight at the time of nutritional status. In adolescents, it is necessary to reduce the frequency of consumption of foods with high IG and to increase the consumption of fruit and vegetables and physical activity, especially in adolescents with DM parents.